Feasibility and safety of shortened hypofractionated high-dose palliative lung radiotherapy – A retrospective planning study. (April 2023) - Jones, Matthew; Rogers, Jane; Kumar Shrimali, Raj; Hamilton, Jo; Athmanathan, Senthil; Jones, Bleddyn
Highlights: Hypofractionated radiotherapy is safe and feasible for palliative lung radiotherapy. Prescriptions of 30 Gy/5# or 30 Gy/6# could be used as an alternative to 36 Gy/12#. A Phase-II study is required to fully assess efficacy for this group of patients. Abstract: Objective: Assess the safety and feasibility of shortened hypofractionated high-dose palliative lung radiotherapy in a retrospective planning study. Methods: Fifteen late stage (III or IV) NSCLC lung radiotherapy patients previously treated with the standard palliative 36 Gy in 12 fractions (12F) schedule were non-randomly selected to achieve a representative distribution of tumour sizes, volumes, and location. Plans were produced using 30 Gy in 5 fractions (5F) and 6 fractions (6F) using a 6MV FFF co-planar VMAT technique. Plans were optimised to meet dose-constraints for planning target volumes (PTVs) and organs at risk (OARs) with established OAR constraints expressed as biological equivalent doses (BEDs). The potential safety was assessed using these BEDs and also with reductions of 10% (BED-10%) and 20% (BED-20%) to account for a reduction in tolerance doses from the effects of chemotherapy or surgery. Results: Mandatory BED constraints were met for all fifteen 5F and 6F plans; BED-10% constraints were met by all 6F plans and six 5F plans. BED-20% constraints were met by six 6F and three 5F respectively. Conclusion: It is potentially safe and feasible to deliver high-dose palliative radiotherapy for late stage NSCLC using the 5F or 6F regimes described, when planned to comparable OAR BEDs as standard radical techniques. It appears toxicity from these regimes should be within acceptable limits provided the dose-constraints described are met. A Phase II study is required to fully assess safety and feasibility, the outcomes of which could reduce the number of patient hospital visits for radiotherapy, thereby benefiting patients and optimising resource utilisation.